Pengaruh Volatilitas Harga Emas terhadap Keputusan Berinvestasi Nasabah: Studi Kualitatif pada Nasabah Bank Syariah - Faizah Gladys Yuniashari; Mohammad Luthfillah Habibi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to explore how gold price volatility influences customers’ investment decisions in Islamic banks within the framework of Islamic values. Employing a qualitative phenomenological approach, the research investigates the perceptions, motivations, and strategies of twelve active customers of Bank Syariah Indonesia in Surabaya through in-depth interviews. The findings reveal that gold price volatility does not necessarily reduce investment interest; instead, it stimulates adaptive and reflective behavior grounded in religious commitment and Islamic financial literacy. Investment decisions are shaped by three main factors: rational risk perception, religious conviction in the permissibility of gold as an Islamic instrument, and trust in the integrity of Islamic financial institutions. Thus, gold price volatility is interpreted not only as an economic signal but also as a social and spiritual phenomenon that fosters financial maturity among investors. The study concludes that faith-driven investment behavior contributes to financial resilience and moral stability amid market uncertainty. These insights enrich the field of Islamic behavioral finance by highlighting the integration of economic rationality and spiritual values in investment decision-making.